VARIASI KADAR GELATIN SEBAGAI BAHAN PENGIKAT PADA FORMULASI NUTRASEUTIKAL SEDIAAN GUMMY CANDIES SARI BUAH BELIMBING MANIS (AVVERHOA CARAMBOLA L) - Feris Firdaus; Selvy Febrina Putri; Fajriyanto Fajriyanto (Teknoin, 2015)
The use of sweet star fruit juice (Averrhoa carambola L.) as a nutraceutical product that contains vitamins A and C are still relatively rare. This research aims to produce dosage gummy candies that can be consumed by the public in a practical and healthy. Gummy candies preparation was made in 5 formulations based on variations in the levels of gelatin as a binder with a ratio of 10%, 12.5%, 15%, 17.5%, 20%. Manufacture of sweet star fruit juice using freeze drying method is performed on the resulting fruit juice. After the sweet star fruit juice formed organoleptic test. Testing the physical properties of gummy candies include organoleptic test, test and test weight uniformity preference level (hedonic test) by the respondent and then the results were compared with the requirements in the literature. Sweet star fruit juice may be formulated into a good nutraceutical product in dosage form gummy candies. Preparations gummy candies sweet star fruit juice produced has met the requirements of a good tablet physical properties, obtained by the coefficient of variation in test weight uniformity to formula 1, 2, 3, 4 and 5, ie 6.40%, 6.37%, 3.65%, 8.93% and 3.77%. Based on the results of organoleptic test, it can be concluded that the formula 3 has the best texture. The test results based preference level (hedonic test), it is known that the formula 3 and 4 preferred/received by the respondents.